Blood Lead Levels among Blood Donors and High-Risk Occupational Groups in a Mining Area in Ghana: Implications for Blood Transfusion among Vulnerable Populations - Veronica Agyemang; Joseph K. Acquaye; Samuel B. E. Harrison; Felix B. Oppong; Stephany Gyaase; Kwaku P. Asante; Edeghonghon Olayemi (Journal of Tropical Medicine)
Lead poisoning has been a major global health problem for decades, and blood transfusion has been suspected as a neglected potential source of lead exposure. Children and pregnant women are most vulnerable to the toxic effects of lead and over 40 percent of blood transfused in Ghana is given to children under 5 years. However, there is little data on the levels of lead in donor blood and the main sources of lead exposure in the Ghanaian population. This study compared blood lead levels (BLL) among selected occupations at risk of lead exposure with healthy blood donors in nonexposed occupations in a Ghanaian mining area. We enrolled 40 participants each from the following high-risk occupational groups: small scale miners, painters/sprayers, drivers/fuel station attendants, and auto-mechanics as well as 40 healthy blood donors (made up of teachers, traders, and office workers). One millilitre of blood was collected from each participant for determination of their BLL, haemoglobin concentration, and blood film morphology. A total of 200 participants made up of 186 (93%) males and 14 (7%) females were enrolled. The mean age of participants was 28.6 ± 8.2 years and their geometric mean (GM) BLL was 6.3 GSD 1.4 µg/dL [95% CI: 6.0 – 6.6]. Participants in high risk occupations had significantly higher GM BLL of 6.7 µg/dL [95% CI :6.4−7.0] compared to 5.0 µg/dL [95% CI: 4.4−5.7] for healthy blood donors [p < 0.001]. The prevalence of elevated BLL (≥5 µg/dL) among the entire study participants, high risk occupations and blood donors was 84.5%, 89.4% and 65% respectively. There was significant association between elevated BLLs and working in an at-risk occupational group [aOR = 3.58, p = 0.014]. Haemoglobin concentration was not significantly associated with elevated BLLs. Basophilic stippling was not observed in any of the blood smears. Blood lead levels were high in blood donors and at-risk occupations in the study area and occupation was associated with elevated BLLs. It is important that measures to safeguard the integrity of donor blood go beyond screening for infectious diseases to include screening individuals in high-risk occupations for lead and other heavy metals to ensure that donor blood from such individuals is safe and does not pose potential danger to the health of vulnerable populations such as children and pregnant women.